KEPUASAN KONSUMEN DESTINASI WISATA TAMAN TEBING BREKSI MELALUI KUALITAS PELAYANAN SEBAGAI VARIABEL MEDIASI - Pertiwi, Angela Titis; Saraswati, Birgitta Dian; Fevriera, Sotya; Siwi, Virgiana Nugransih; Agilita, Yuliana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
Research on consumer behavior is important in the world of business, including in the filed of tourism business. One of the tourism objects that is relatively new so that it still needs suggestions from researches for its development is Breksi Cliff in Sleman Regency. This research aims to study the effect of personal value on service quality and the effects of personal value and service quality on the satisfaction of Breksi Cliff tourists. This research used Partial Least Squares-Structural Equation model approach which was built from a sample of 200 tourists which was collected through a survey in Breksi Cliff. This research found that personal value affects service quality, that service quality affects tourist satisfaction and that personal value influences tourist satisfaction both directly and indirectly through service quality.